Increasing seawater temperatures in the Levantine Basin, eastern Mediterranean, may elicit increased activity in slipper lobsters, Scyllarides latus (Latreille, 1803) (Decapoda: Achelata: Scyllaridae). Issue 4 (11th January 2023) - Goldstein, Jason S; Spanier, Ehud
Abstract: Temperature is a predominant motivator for movement and activity over a wide range of mobile marine ectotherms. Water temperature modulates the movements of many lobster species, which can vary widely over spatial and temporal scales. Providing insight into the thermal preferences (and refuges) that some lobsters seek remains a key tenet to our understanding of the behavioral ecology of these animals. The Mediterranean slipper lobster, Scyllarides latus (Latreille, 1803 ), shows seasonal movements throughout most of its range and is subject to a changing thermal environment. Through a series of laboratory-based trials, we examined the movement activity of S. latus and tested the hypothesis that S. latus engage in increased movements when subjected to temperatures outside their preferred range. To examine this, we exposed a set of lobsters ( N = 10, CLavg = 83.1 ± 6.1 cm) to the same thermal profiles as in the field and assayed their locomotion using activity wheels. Our laboratory results showed that individuals of S. latus are more active at higher temperatures during dawn hours and revealed that warming water temperatures elicited markedly longer movements over a similar timeframe. Combined, these findings suggest that increasing water temperatures in the eastern Mediterranean (Levant) may affect lobster movements and could alter seasonal patterns of distribution as well.